Cost-effectiveness of a national immunization program with the 13-valent pneumococcal conjugate vaccine compared with the 10-valent pneumococcal conjugate vaccine in South Korea. Issue 3 (4th March 2021) - Kim, Hye-Young; Park, Seong-Beom; Kang, Eun-Sil; Lee, Sang-Min; Kim, Hyun-Jin; Wasserman, Matt
ABSTRACT: Introduction: Globally, pneumococcal disease represents a significant burden. South Korea implemented the 7-valent pneumococcal conjugate vaccine (PCV7) in 2003, replaced with the 10-valent (PCV10) and 13-valent (PCV13) vaccine in 2010. In 2014, both vaccines were introduced in the national immunization program (NIP) for infants with 3 primary doses and one booster dose We performed a cost-effectiveness evaluation to elucidate which vaccine may be expected to provide greater impact if included in a NIP. Methodology: Using an established model, we estimated the impact of introducing either PCV13 or PCV10 into the South Korean NIP in 2015. Vaccine impact was based on historic observed impact of PCV13 from 2010 to 2015 in Korea given high uptake of PCV13, and PCV10 impact was estimated based on experiences in countries using PCV10. Incidence and costs for all ages and including invasive pneumococcal disease, pneumonia, and acute otitis media were derived from the literature and Health Insurance Review and Assessment database. Results: In the base-case, over 5-years PCV13 was estimated to avert 550, 000 more cases of pneumococcal disease compared to PCV10, driven by broader serotype coverage and less replacement due to serotypes 3 and 19A. This translated to a cost-savings of $47.4 million USD despite PCV13's higher cost. Sensitivity analysis found incremental cost-effectiveness ratios (ICERs) ranged from cost-saving to $7, 300 USD per quality-adjusted life year (QALY). Conclusion: A NIP using PCV13 was estimated to have a more substantial public health impact and be cost-saving compared to a program with PCV10 due to broader serotype coverage.